Identification and characterization of abamectin resistance in Tetranychus urticae Koch populations from greenhouses in Turkey. (October 2018) - Çağatay, Naciye Sena; Menault, Pauline; Riga, Maria; Vontas, John; Ay, Recep
Abstract: The two-spotted spider mite, Tetranychus urticae Koch is one of the most serious pests in greenhouses and has developed high resistance to many classes of acaricides rapidly. Three T. urticae populations were collected from vegetable greenhouses in Antalya and Muğla, Turkey. These populations showed high resistance levels to abamectin ranging between 223 and 404 fold compared to a susceptible population. The interaction of some synergists (piperonyl butoxide; PBO, diethyl maleate; DEM and S-benzyl O, O-diisopropyl phosphorothioate; IBP) with abamectin was analyzed showing possible implication of esterases in resistances in the three populations studied. The activities of esterase, glutathione S-transferase (GST) and cytochrome P450 (p450) was determined using α-naphthyl acetate, 1-chloro-2, 4 dinitrobenzene (CDNB) and 7-ethoxycoumarin (7-EC) as substrates, respectively. In all field populations, esterase, glutathione S-transferase and P450 activities were higher, when compared to the susceptible population (GSS). The presence of known abamectin resistance target site mutations (G314D and G326E) on the glutamate gated chloride channels was also examined. However, no target site–resistance mutation was detected in all three populations. According to our results, detoxification enzymes, but no target site intensivity seem to play role in abamectin resistance in field T. urticae populations from Turkey. Highlights: We collected 3 Tetranychus urticae populations from different greenhouse crops in Turkey. The resistance ratios to abamectin were determined in T. urticae field populations, in comparison with susceptible strain. DEM, IBP and PBO synergists increased the efficiency of abamectin in all T. urticae populations. Detoxification enzymes can be considered important in the development of abamectin resistant T. urticae populations. No target site resistance mutation was detected.